Perception of the Health Threats Related to the Consumption of Wild Animal Meat—Is Eating Game Risky? - Niewiadomska, Katarzyna (Foods, 2021)
Consumer interest in game meat has increased in recent years. Consumers appreciate its nutritional value but still have many concerns. Based on data from a quantitative study conducted in the group of 450 purposively selected Polish respondents declaring to consume the game meat, consumers were segmented concerning the perception of health risks associated with its consumption. Three separate clusters were identified using hierarchical cluster analysis: Indifferent (42%), Fearful (30%), and Selective (28%). The clusters differed significantly in the perception of the role of game in their lives and taking actions to mitigate the health risks associated with its consumption. In addition, their socioeconomic profiles were significantly different. The Indifferent segment—significantly more often than the other segments—believes that game has a positive impact on health, and the way to counteract the health risks is to not eat raw meat. The Selective segment attaches great importance to the choice of consumption place as a warranty of access to safe meat. The Fearful segment is willing to pay more for good quality meat and search for information. The results proved that the game consumers are not a homogenous group. Recognizing the differences can indicate a path for the traders to efficiently meet the consumers’ expectations and needs.